Space conjugation induced white light and room-temperature phosphorescence from simple organic small molecules: single-component WLED driven by both UV and blue chips. (11th August 2021) - Zheng, Xin; Huang, Yuanshan; Xiao, Duoduo; Yang, Shuming; Lin, Zhenghuan; Ling, Qidan
Abstract : Simple molecule TIM with planar conformation and rich heteroatoms exhibits white emission and yellow phosphorescence for space conjugation. TIM powder can be employed as a single-component material to fabricate WLEDs driven by both UV and blue chips. Abstract : Unique luminescence of non-conventional luminophores derived from space conjugation (SC) has recently attracted extensive interest. However, it is difficult to achieve highly efficient emission (especially a white light one) from SC, due to the rotational, vibrational motions of the functional groups. Herein, two simple molecules, 3, 4-thiophene dicarboxylic imide (TIM) and 3, 4-thiophene dicarboxylic anhydride (TAD) with a rigid and planar structure, and rich heteroatoms, are employed to respectively construct two SC systems. Both the TIM and TAD exhibit aggregation induced emission (AIE) and excitation-wavelength dependence emission in concentrated solution and crystals because of different aggregates formed through SC. Under excitation of 365 nm UV light, TIM and TAD show a warm and cold white emission with decent quantum yield up to 27%, respectively. Interestingly, TIM and TAD can produce yellow room temperature phosphorescence (RTP) at around 585 nm with the lifetime of 44 ms and 39 ms, respectively, due to the existence of heteroatoms and carbonyl groups. Compared with TAD, TIM crystals display stronger intermolecular interactions, which make its ground powder inherit the effective white emission of crystal, because the SC is not destroyed by an external force. Consequently, TIM is of huge potential in the application of white light-emitting diodes (WLEDs). Two types of single-component WLED based on TIM, driven by both UV and blue chips, give white light with CIE of (0.31, 0.39) and (0.33, 0.35), respectively. To the best of our knowledge, TIM should be the simplest single molecule white-light material applied in WLED.